L'irrecevabilité du projet de modification de l'article 96 de la Loi constitutionnelle de 1867 - Pépin, Gilles (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In this paper, the author demonstrates that section 96 of the Constitution Act, 1867 is a source of political tensions. The « rules of the game » in construing section 96 are well known but are neither clear nor precise. The government has proposed a section 96B which should be relevant today as well as in the next century, but the new section should not be an obstacle to necessary changes in the judicial and administrative systems. Nevertheless, the new section 96B runs the risk of replacing one constitutional problem by another one. If section 96B was to be enforced, the Legislature could give any judicial function, old or new, to an « authority other than a court », subject to judicial control of the function. By writing an amendment to section 96, consideration must be given to sections 97 to 101, which are also part of the « Judicature » Chapter in the Constitution Act, 1867. In keeping with the author's thinking, some changes may be made to present law, which would be preferable to the proposed amendment.